Evaluating the effectiveness of DAP as a consolidant on Turkish building stones - Celik, Selen Ezgi; Gulen, Jale; Viles, Heather A. (ELSEVIER SCI LTD, 2020)
DAP is a new, bio-inspired consolidant already proven to be useful for limestones. In this study, we investigate the effectiveness of DAP on four different types of Turkish stones; Ankara (andesite), Bitlis (andesite), Mardin (limestone) and Nevsehir (ignimbrite). The effectiveness was analysed by means of weight, water absorption, surface hardness, surface roughness, color change, UPV and DRMS measurements. The DAP treated samples were exposed to weathering and a control set treated with TEOS for comparison. The DAP treatment performed comparably to TEOS resulting in an overall improvement in mechanical properties, without significantly altering water absorption or colour properties. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Stone conservation; Consolidant; DAP; TEOS; Weathering; Limestone; Ignimbrite; Andesite; HISTORICAL BUILDINGS; AMMONIUM PHOSPHATE; SUGARING MARBLE; HYDROXYAPATITE; CONSERVATION; SILICATE; OXALATE; HERITAGE; PATINAS; FILMS; Construction & Building Technology; Engineering; Materials Science